Pengaruh Kejelasan Sasaran Anggaran, Penerapan Akuntansi Sektor Publik, Pengendalian Akuntansi Terhadap Akuntabilitas Kinerja Instansi Pemerintah Desa (Studi Kasus Pada Pemerintahan Desa di Kecamatan Banyudono) - Retno Putri Hastuti; Hadi Samanto; Yuwita Ariessa Pravasanti (Jurnal Akuntansi dan Pajak, 2027)
This study aims to analyze the effect of budget target clarity, public sector accounting implementation, and accounting control on the performance accountability of village government agencies in Banyudono District. The method used in this study is quantitative. Data were obtained from distributing questionnaires to predetermined respondents using saturated sampling techniques. Data analysis techniques used in this study include descriptive statistics of respondents, validity tests, reliability tests, classical assumption tests, and multiple linear regression analysis. The results of the study indicate that budget target clarity has a negative and significant effect on the performance accountability of government agencies with a calculated t of -4.655 which is absolutely greater than the t table of 1.658 and a significance of 0.000 <0.05. The application of public sector accounting has a significant effect on the performance accountability of government agencies with a calculated t value of 5.640 > t table of 1.658 and a significance of 0.000 <0.05. Accounting control has a significant influence on the performance accountability of government agencies, with a calculated t-value of 8.912 > t-table 1.658 and a significance level of 0.000 < 0.05). Keywords: Accountability, Accounting Control, Budget Target Clarity, Implementation of Public Sector Accounting, Village Government